Lovastatin for the Treatment of Adult Patients With Dengue: A Randomized, Double-Blind, Placebo-Controlled Trial - Simmons, Cameron (2018)
BACKGROUND: Dengue endangers billions of people in the tropical world, yet no therapeutic is currently available. In part, the severe manifestations of dengue reflect inflammatory processes affecting the vascular endothelium. In addition to lipid lowering, statins have pleiotropic effects that improve endothelial function, and epidemiological studies suggest that outcomes from a range of acute inflammatory syndromes are improved in patients already on statin therapy. METHODS: Following satisfactory review of a short pilot phase (40 mg lovastatin vs placebo in 30 cases), we performed a randomized, double-blind, placebo-controlled trial of 5 days of 80 mg lovastatin vs placebo in 300 Vietnamese adults with a positive dengue NS1 rapid test presenting within 72 hours of fever onset. The primary outcome was safety. Secondary outcomes included comparisons of disease progression rates, fever clearance times, and measures of plasma viremia and quality of life between the treatment arms. RESULTS: Adverse events occurred with similar frequency in both groups (97/151 [64%] placebo vs 82/149 [55%] lovastatin; P = .13), and were in keeping with the characteristic clinical and laboratory features of acute dengue. We also observed no difference in serious adverse events or any of the secondary outcome measures. CONCLUSIONS: We found lovastatin to be safe and well tolerated in adults with dengue. However, although the study was not powered to address efficacy, we found no evidence of a beneficial effect on any of the clinical manifestations or on dengue viremia. Continuing established statin therapy in patients who develop dengue is safe.Chinese Clinical Trials Registration.ΓÇâISRCTN03147572.